2021
DOI: 10.1051/e3sconf/202131803009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Structural Behavior of Double Channel Castellated Steel Beams

Abstract: The main idea of castellated steel beams is to reduce their weight by creating void space (web holes) in the main beam body. This structure tends to exhibit superior properties such as advanced strength, lightweight, and cost-saving compared to the amount of steel used compared with reference beam without web holes. This study is devoted to investigating the structural behavior of double-channel cast steel beams. In this project, two pieces of a rolled hot steel channel were connected to form a new section use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Beams produced by the castellation method were 50% higher than the original beam, increased moment capacity by up to 40% without the use of steel, and increased load capacity by making the beams lighter [6]. In Khaleel and AL-Shamaa [7]'s study, five specimens of 2C-shapes beam with different shapes and numbers of openings web, and this study showed that bearing strength decreases when the web holes are few. As the number of web holes increased to a specific limit, the bearing strength continued to rise, and if openings exceeded a specific limit, the bearing force decreased; the rate of increase in the bearing force was found to be between 17.7% to 40.0%.…”
Section: Introductionmentioning
confidence: 93%
“…Beams produced by the castellation method were 50% higher than the original beam, increased moment capacity by up to 40% without the use of steel, and increased load capacity by making the beams lighter [6]. In Khaleel and AL-Shamaa [7]'s study, five specimens of 2C-shapes beam with different shapes and numbers of openings web, and this study showed that bearing strength decreases when the web holes are few. As the number of web holes increased to a specific limit, the bearing strength continued to rise, and if openings exceeded a specific limit, the bearing force decreased; the rate of increase in the bearing force was found to be between 17.7% to 40.0%.…”
Section: Introductionmentioning
confidence: 93%